Malaysian teachers’ overall willingness to communicate during classroom discussion and factors affecting their communication interactions - Jahedi, Maryam (2021)
Willingness to Communicate (WTC) is defined as language learners’ willingness to use the opportunities for authentic communication which has received considerable attention in the field of second language acquisition as it brings together the factors that can describe and predict L2 communication (Cao & Philp, 2006; Kang, 2005; MacIntyre et al., 1998; Peng, 2007). Most of these studies were mainly conducted through self-report questionnaires and few of them focused on the situational factors affecting learners’ WTC. This study is significant as it investigates teachers’ overall WTC and their WTC during the classroom discussion. The willingness to communicate model and discourse analysis were employed to examine Malaysian English teachers’ overall WTC and communication behavior. Therefore, their interactions during the classroom were video- and audio-recorded and journal entries were collected. Moreover, two questionnaires were administered, and an interview was conducted. The WTC Model explained why they do or do not participate in the classroom discussion, and discourse analysis helped to describe their communication behavior. The results of the study revealed that the teachers’ general WTC was not consistent with their L2 use during the classroom discussion. The study also found affecting situational WTC factors, which include classroom-contextual factors, interpersonal influencing factors and linguistic-related factors. The major speech functions were questions and statements, which indicates that WTC was displayed through the predominant use of declaratives and interrogatives. Moreover, the study found the predominant interactional resources used to display WTC. The study will benefit learners since the affective WTC factors in the L2 can be made known to the learners, which can increase their engagement in the classroom interactions. Moreover, the outcomes of the study are expected to provide insights for teachers about the factors that affect learners’ WTC in the L2 so that they can modify their instructions to encourage learners’ WTC.